Formation of pedagogical skills of teachers in non-pedagogical universities abroad and in Ukraine (Pedagogy of Higher and Secondary Education, 2014)
Gunko N. A. Formation of pedagogical skills of teachers in non-pedagogical universities abroad and in Ukraine.On the basis of analysis and systematization of scientific information the notion of pedagogical skills and its importance in pedagogical practice is revealed. The author gives the characteristic of teacher training and formation of pedagogical skills of teachers in non-pedagogical universities abroad and in Ukraine.
Keywords: pedagogical skills; non-pedagogical higher educational establishments; seminars; workshops; teaching motivation